2017
DOI: 10.4239/wjd.v8.i5.202
|View full text |Cite
|
Sign up to set email alerts
|

Association between dairy intake, lipids and vascular structure and function in diabetes

Abstract: AIMTo determine lipid species that change in response to a change in dairy consumption. In addition, to investigate whether dairy associated lipid species are correlated with changes in measures of vascular structure and function.METHODSA 12-mo randomised controlled trial was conducted to determine the effect of increased consumption of fruit, vegetables and dairy, compared to usual diet, on measures of vascular structure and function in adults with type 1 and type 2 diabetes (n = 108). This paper comprises po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…We found lyso-PC 15:0 as the most discriminating lyso form in the MH-LDL-c group. This finding was accompanied by strong positive associations with classical lipidrelated markers such as TC, LDL-cholesterol and the atherogenic index LDL-cholesterol/HDL-cholesterol, which is similar to previous human studies reporting a link for lyso-PC 15:0 to the incidence of type 2 diabetes [28] and increased diastolic BP [29]. Nonetheless, our finding provides an added link of lyso-PC 15:0 to lipid disorder highlighting its possible role as susceptibility/risk biomarker for HC.…”
Section: Discussionsupporting
confidence: 89%
“…We found lyso-PC 15:0 as the most discriminating lyso form in the MH-LDL-c group. This finding was accompanied by strong positive associations with classical lipidrelated markers such as TC, LDL-cholesterol and the atherogenic index LDL-cholesterol/HDL-cholesterol, which is similar to previous human studies reporting a link for lyso-PC 15:0 to the incidence of type 2 diabetes [28] and increased diastolic BP [29]. Nonetheless, our finding provides an added link of lyso-PC 15:0 to lipid disorder highlighting its possible role as susceptibility/risk biomarker for HC.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, several recent lipidomic profiling studies showed a negative correlation between LDL levels and the occurrence of cardiovascular diseases [ 51 , 52 , 53 ]. In addition, diabetes is an important risk factor for cardiovascular diseases; however, conflicting results have been reported on the correlation of LPC and diseases [ 4 , 70 , 71 , 72 , 73 ].…”
Section: Lysophosphatidylcholine and Human Diseasesmentioning
confidence: 99%
“…Furthermore, higher levels of circulating LPC could reflect a lower rate of atherogenic lysophosphatidic acid production via autotaxin-mediated LPC hydrolysis, thus conferring a net protective effect on CVD [38] . Therefore, in conjunction with recent epidemiological evidence associating dairy consumption with changes in circulating LPC 17:0 [39] , an abundance of genetic, epidemiologic, functional, and biochemical data implicating LPCs in CVD suggest that mechanistically understanding the enzyme kinetics and complexities of LPC metabolism may highlight promising therapeutic targets.…”
Section: Lysoglycerophospholipid Markers Of Metabolic Traitsmentioning
confidence: 99%